MEWUJUDKAN MANUSIA PARIPURNA DENGAN STRATEGI PENDIDIKAN HOLISTIK DALAM MEMBENTUK SOSOK MANUSIA YANG SEUTUHNYA - Weni Yulastri; Yusparni Yetti; Febrio Rozalmi Putra; Putri Yulia Mandasari; Mulya Syafrina; Wendri Gusdi; Seri Sufani (STKIP Subang, 2025)
Holistic education is an approach that views learners as whole human beings who possess physical, emotional, intellectual, social, and spiritual dimensions. This study aims to explore educational efforts needed to shape a complete human being through character strengthening, social-emotional development, intellectual competence, and spiritual sensitivity. Using the literature review method, the study concludes that holistic education requires integrated pedagogical strategies that involve schools, families, and communities. Its implementation improves student well-being, strengthens identity, and prepares them to face the challenges of the 21st century.